A MULTIOBJECTIVE GENETIC ALGORITHM FOR SOLVING RELIABILITY OPTIMIZATION PROBLEM OF A COMMUNICATION NETWORK SYSTEM - MUKUDA, MINORU; TSUJIMURA, YASUHIRO (Advanced Reliability Modeling II, 2006)
In this paper, first, we formulate a reliability optimization problem in which unavailability of a communication network system is minimized, and next, we propose a multiobjective Genetic Algorithm (mo-GA) for solving the reliability optimization problem. In order to obtain high efficiency of searching non-dominated solutions, we combine the Improved Saving Pareto solutions Strategy (ISPS) and the adoptive Local Search (LS) with the multiobjective Genetic Algorithm. Through some numerical experiments, we evaluate the reliability optimization problem of a communication network system, and show effectiveness of the multiobjective Genetic Algorithm.